Urelementets musik: Litterære præciseringer af musikkens væsen - Nielsen, Erik A. (Danish Yearbook of Musicology, 1981)
At the end of the 19th century music is in many ways a theme and a dream for the art of literature. Writers around the turn of the century portray it, in continuation of Søren Kierkegaard's famous definition of music as demoniacal, as an element of passion in which could be lived the life of erotic emotions which the strict moral code of the times otherwise made so difficult. This view is illustrated by Wagner's Tannhäuser, which in Denmark found expression in, among others, Holger Drachmann's novel of the same name. Furthermore, it is associated with an intense interest in demoniacal-musical creatures such as fauns. The figure which is so well known from Debussy's Prelude is found again in Jakob Knudsen's novel Gjæring, where it is interpreted in connection with an analysis of Arnold Bocklin's visual representations of nature's elementary beings. The slow rate of liberation of the demoniacal quality is of some significance for the impetus, the artistic energy, which brings musical works of art into being. The »epic«, forward-directed compositions are replaced by a vegetating sound-world, of which Debussy in particular is a leading exponent. With this we are in the musical world which the French symbolists tried to set free with their poetic language. Music becomes a kind of vision or dream-picture for writers, especially poets. As a sort of reaction against this vegetating sound-world, so lacking in energy, there appears around the turn of the century a kind of biological energy which is cosmically synchronized, that is, which is related to the rising of the sap in the spring and to earth's annual circuit around the sun. Thøger Larsen and Johannes V. Jensen are the literary examples, Carl Nielsen the musical. A kind of biological ecstasy arises from his music. Eventually the origin of the quality of dissonance is treated, for an interpretation of which the poetry of Johannes V. Jensen and Sophus Claussen provides an opportunity. To use a Nietzschian expression, it is man himself who has come into a dissonant relationship with the world order, and the young Johannes V. Jensen attempts in his poems to accept the dissonance (» The Interference «) as the seat of consciousness itself. Sophus Claussen speaks of »the music of the primordial element« as a way of describing the tremendous cosmic nature, which scornfully refuses to take notice of mankind's civilized work on the earth. The original element resounds in a mighty dissonance with everyday life. This is musically exemplified in Stravinsky's Sacre. All things considered, the lecture is an attempt to see the beginnings of musical modernism in the light of corresponding developments in philosophy, poetry and painting. A suggestion is also made towards the understanding of three musical concepts: 1. sound, 2. musical impetus i.e. composition, and 3. dissonance .